2009
DOI: 10.1590/s0104-42302009000200018
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao peso insuficiente ao nascimento

Abstract: The risk for insufficient birth weight was higher for female newborn, offspring of primiparous women, of women who had inadequate prenatal care and had vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0
18

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
3
3
0
18
Order By: Relevance
“…Antonio et al 26 observed similar results in their study, and hypothesized that as lower weight gain may be associated with a lower socioeconomic level, women belonging to this socioeconomic stratum are commonly users of the Unified Health System (Sistema Único de Saúde - SUS) in Brazil, which imposes limitations on the performance of cesarean deliveries, justifying a lower chance of underweight (2,500g to 2,999g) in cesarean births. According to Carniel et al ,27 there is a higher cesarean section rate in groups of low obstetric risk and women of higher socioeconomic status, suggesting that the criteria for the indication of this procedure are not purely technical.…”
Section: Discussionsupporting
confidence: 58%
“…Antonio et al 26 observed similar results in their study, and hypothesized that as lower weight gain may be associated with a lower socioeconomic level, women belonging to this socioeconomic stratum are commonly users of the Unified Health System (Sistema Único de Saúde - SUS) in Brazil, which imposes limitations on the performance of cesarean deliveries, justifying a lower chance of underweight (2,500g to 2,999g) in cesarean births. According to Carniel et al ,27 there is a higher cesarean section rate in groups of low obstetric risk and women of higher socioeconomic status, suggesting that the criteria for the indication of this procedure are not purely technical.…”
Section: Discussionsupporting
confidence: 58%
“…Analysis of the certificates of live births revealed the following risk factors for the underweight at birth (between 2,500 and 2,999 g): female newborns, children of primiparae, inadequate prenatal care, and vaginal delivery [29]. In the present study, according to this classification, there were 18 AIG (56.2%), 11 (34.4%) LGA, and 3 (9.4%) SGA infants (detailed data not provided).…”
Section: Discussionmentioning
confidence: 52%
“…Em Campinas, esta proporção se mantém inalterada desde os anos 1990 (6,21) . Em 2001, para o Brasil, estado de São Paulo e região de Campinas, essas distribuições são semelhantes (22,3%, 25,1% e 24,7%, respectivamente).…”
Section: Tabela 4 -unclassified
“…Encontrou-se alto percentual de gravidez na adolescência, parto cesáreo e peso inadequado ao nascimento, sobretudo nas regiões com piores índices de condição de vida (5,6) . Assim, este trabalho teve como objetivo comparar os dados pré-natais e dos partos das mulheres de Para avaliar a associação entre as variáveis, utilizou-se o teste de qui-quadrado.…”
Section: Introductionunclassified